2015
DOI: 10.1016/j.ejps.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fasted state human intestinal fluid as apical solvent system in the Caco-2 absorption model and comparison with FaSSIF

Abstract: To date, the Caco-2 model is considered as the gold standard to predict intestinal drug absorption. Often, aqueous phosphate buffers are used as apical medium. The purpose of this study was to use fasted state human intestinal fluid (FaHIF) as apical solvent system to generate biorelevant permeability values for a series of 16 model drugs that can be used as reference data to critically evaluate fasted state simulated intestinal fluid (FaSSIF) as possible substitute medium. Caco-2 compatibility with FaHIF was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…The compatibility of Caco-2 cell monolayer against FaSSIF and/or HP-b-CD is controversial. 20,50,[52][53][54][55] Thus, Caco-2 cell monolayer integrity was checked by TEER values and lucifer yellow permeability in this study. As shown in Table 3, less than 15% of reduction of TEER and acceptable lucifer yellow permeability (<1 Â 10 À6 cm/s) indicated that Caco-2 cell monolayer kept its tightness in all tested groups.…”
Section: Discussionmentioning
confidence: 99%
“…The compatibility of Caco-2 cell monolayer against FaSSIF and/or HP-b-CD is controversial. 20,50,[52][53][54][55] Thus, Caco-2 cell monolayer integrity was checked by TEER values and lucifer yellow permeability in this study. As shown in Table 3, less than 15% of reduction of TEER and acceptable lucifer yellow permeability (<1 Â 10 À6 cm/s) indicated that Caco-2 cell monolayer kept its tightness in all tested groups.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] Because these media are supplemented with biorelevant substances like taurocholate and lecithin, they are preferred over simple aqueous buffers. Wuyts et al 37,38 previously validated the use of FaSSIF as biorelevant apical substitute medium for FaHIF in the Caco-2 cell assay and the Ussing chambers setup. 33 To verify whether FaSSIF can be considered as a valuable substitute for FaHIF in the AMIsystem, both human and simulated intestinal media were explored as donor solvent system.…”
Section: Correlation Between Fassif and Fahif As Donor Medium In The mentioning
confidence: 99%
“…40 In this study, FaSSIF-v1 was used as donor medium because of (i) its simplicity and (ii) the strong correlation observed with FaHIF using other permeation tools (Caco-2 system and Ussing chambers model). 37,38 Nevertheless, it may be worthwhile to explore the passive permeability using FaSSIF-v2 and FaSSIF-v3 as donor medium in the AMI-system. 41…”
Section: Correlation Between Fassif and Fahif As Donor Medium In The mentioning
confidence: 99%
“…P app and TEER measurements have been used extensively to evaluate monolayer integrity of Caco-2 cells ( 11 , 12 , 19 , 20 ). These parameters correlated well in this study (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been used previously by Wuyts et al . who applied a barrier of mucin onto Caco-2 cells to protect them against fasted state human intestinal fluids ( 20 ). The concentration they used in their study was insufficient to completely protect the cells against some of the damaging effects, and so a larger amount of mucin was applied in this study (200 μL of 150 mg/mL mucin).…”
Section: Discussionmentioning
confidence: 99%